Assessment of two species of macrophytes as biomomitors of heavy metals in rivers of Córdoba, Argentina - Harguinteguy, Carlos Alfredo (2011)
Direct discharge or wet and dry air depositions of contaminants increase the concentrations of trace elements in aquatic systems, thus resulting in their accumulation in sediments. Aquatic plants absorb elements through roots and/or shoots and in water quality studies they may be useful biomonitors. The aim of this study was to evaluate two macrophytes species, Stuckenia filiformis and Potamogeton pusillus as bioindicators of heavy metal pollution and their spatial variation in rivers of the province of Córdoba. The sampling was carried out in the rivers Ctalamochita and Suquía of the province of Córdoba. The elemental composition of S. filiformis and P. pusillus leaves was determined using Total Reflection X-ray Fluorescence with Synchrotron Radiation (SR-TXRF). In all cases significant differences were found between the sampling sites, except for Ni concentrations. S. filiformis and P. pusillus accumulated the highest levels of Cu, Pb and Zn in the city of Río Tercero. Moreover, Zn concentrations were significantly higher in the site located after the city. As for the Suquía river, the highest values of Cu, Pb and Zn were found after the city of Córdoba. The species S. filiformis and P. pusillus behaved as effective biomonitors of aquatic quality.